Private foundations : tax law and compliance - Hopkins, Bruce R.; Blazek, Jody (Wiley nonprofit authority series., 2014)
"Private foundations, although constituting a relatively small portion of the charitable community, are burdened with extensive federal tax law requirements that belie their numbers, and substantially regulate and circumscribe their operations. This body of law has steadily grown since its inception as a considerable portion of the Tax Reform Act of 1969. This book came about in reflection of this expanding and expansive aspect of the law pertaining to these unique forms of tax-exempt organizations. We have attempted to both capture and summarize this law, and to provide guidance as to compliance with it"--